Investigating Stress Transfer Between the Tuz Gölü Fault Zone and Hasan Dağ Volcano (Turkey) - Hedger , Emily; Gottsmann , Jo (Frontiers in Earth Science, 2022)
The 27 km long Akhisar-Kilic ̧ fault segment (AKFS) of the seismically active Tuz Go ̈lu ̈ fault zone in the Central Anatolian Volcanic Province transects the north-eastern flank of the active Hasan Dag ̆ volcanic complex. Elevated footwall uplift rates in the vicinity of Hasan Dag ̆, and the surpassing of the calculated recurrence interval for fault segment rupture may indicate system criticality. Here we use Finite Element Analysis to quantify the Coulomb failure stress transfer between the fault segment, conjugate fault systems and Hasan Dag ̆’s magma reservoir, accounting for stress modulation by both topography and a mechanically heterogeneous crust. The magnitude of current stress accumulation by aseismic slip on the AKFS since its most recent rupture (5.45 ka±0.16 BP) is parameterised using the Coulomb Failure Stress change (∆CFS). The model predicts a currently accrued ∆CFS of between 2.5±0.2 and 15±0.5 MPa3 on the fault plane for published lower and upper-bound estimates of right-lateral aseismic slip rates, respectively, and sufficient to promote failure of the segment. We show that protracted aseismic slip contributes to the progressive unclamping and transtensional opening of potential magma pathways oriented perpendicularly to the AKFS both above and below the reservoir thereby encouraging reservoir failure with potential for magma ascent to feed an eruption. The M5.1 20th of September 2020 earthquake SW of Hasan Dag ̆ occurred in a volume predicted by this study to have undergone fault unclamping due to aseismic slip along the AKFS. Earthquake magnitudes of between Mw5.94 and Mw6.76 due to hypothetical partial or complete rupture of the segment would further unclamp fractures perpendicular to the AKFS beneath and above the magma reservoir.. For the same range of moment magnitudes, modelled (∆CFS) both below and above the reservoir indicate clamping of fractures parallel to the AKFS. We find that the spatial pattern of (∆CFS) on Hasan Dag ̆’s magma reservoir is predominantly controlled by the location of rupture relative to the reservoir with the magnitude of the earthquake playing a subordinate role. We explore implications of our findings for the assessment of interconnected seismo-volcanic hazards and associated risks.